2020
DOI: 10.1007/s11666-020-01077-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Diffraction Study of Macrostress and Microstress in Al-Al2O3-Based Corrosion Protection Coating Obtained by Cold Spray (Dynamic Metallization)

Abstract: Protective coatings based on an Al-Al 2 O 3 metal matrix composite (MMC) were sprayed using dynamic metallization (DM), a low-pressure cold spray variant. A series of samples approximately 1 mm in thickness were sprayed using different spray process parameters (temperature, velocity) and different feedstock powder compositions (Al, Zn, Al 2 O 3 ). This resulted in MMCs of different phase compositions and slightly different physical conditions of coating formation. The through-thickness residual stresses that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…As will be seen through examples below, neutron sources have been regularly used to study residual strains in thermally sprayed and cold sprayed coatings. For coated samples -SANS QUOKKA (monochromatic) § -USANS KOOKABURRA (monochromatic) § Ni, Ni-29%Cr, WC-17%Co [47]; Inconel 625 [48]; Ni-914-3 [50]; AA-6061-T6 [51]; Ti [52]; Inconel®718 [53]; Cu, Al [62]; YSZ [72] 0.2 × 0.2 × 15 mm 3 (and 0.3 mm) [47]; 0.2 × 0.2 × 20 mm 3 [48,50]; 0.5 × 0.5 × 18 mm 3 [51]; 0.5 × 0.5 × 20 mm 3 [52]; 1 × 1 × 1 mm 3 Ni + 5%Al [58]; IN625 alloy [59]; Al, Si, Mo 2 C-Mo [60]; Mo [61]; Cu, Al [62]; Al [63]; Al-Al 2 O 3 [64]; 0.5 × 0.5 × 7 mm 3 [39]; 1 × 1 × 7 mm 3 [58]; 2 × 2 × 7 mm 3 [59]; 0.5 × 0.5 × 18 mm 3 [62]; 0.5 × 0.5 × 7 mm 3 of various thicknesses, investigators have used various gauge volumes with slit widths (0.2 mm, 0.3 mm, 0.5 mm) in through thickness dimension. Interestingly, different strategies were considered to obtain strain-free lattice parameter ( d 0 hkl ) for the coating and substrate part.…”
Section: Strain Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As will be seen through examples below, neutron sources have been regularly used to study residual strains in thermally sprayed and cold sprayed coatings. For coated samples -SANS QUOKKA (monochromatic) § -USANS KOOKABURRA (monochromatic) § Ni, Ni-29%Cr, WC-17%Co [47]; Inconel 625 [48]; Ni-914-3 [50]; AA-6061-T6 [51]; Ti [52]; Inconel®718 [53]; Cu, Al [62]; YSZ [72] 0.2 × 0.2 × 15 mm 3 (and 0.3 mm) [47]; 0.2 × 0.2 × 20 mm 3 [48,50]; 0.5 × 0.5 × 18 mm 3 [51]; 0.5 × 0.5 × 20 mm 3 [52]; 1 × 1 × 1 mm 3 Ni + 5%Al [58]; IN625 alloy [59]; Al, Si, Mo 2 C-Mo [60]; Mo [61]; Cu, Al [62]; Al [63]; Al-Al 2 O 3 [64]; 0.5 × 0.5 × 7 mm 3 [39]; 1 × 1 × 7 mm 3 [58]; 2 × 2 × 7 mm 3 [59]; 0.5 × 0.5 × 18 mm 3 [62]; 0.5 × 0.5 × 7 mm 3 of various thicknesses, investigators have used various gauge volumes with slit widths (0.2 mm, 0.3 mm, 0.5 mm) in through thickness dimension. Interestingly, different strategies were considered to obtain strain-free lattice parameter ( d 0 hkl ) for the coating and substrate part.…”
Section: Strain Analysismentioning
confidence: 99%
“…Using the BT8 instrument at NIST, Luzin et al [64] investigated residual stresses in low-pressure cold sprayed coatings (e.g., Al-Al 2 O 3 metal matrix composite) of 1 mm thickness onto 3 mm thick A16061 aluminium substrate. A gauge volume 0.5 × 0.5 × 20 mm 3 was used and applied equal-biaxial stress approach to obtain residual stresses.…”
Section: Strain Analysismentioning
confidence: 99%
“…Using the BT8 instrument at NIST, Luzin et al [55] investigated residual stresses in low-pressure cold sprayed coatings (e.g., Al-Al2O3 metal matrix composite) of 1 mm thickness onto 3 mm thick A16061 aluminium substrate. A gauge volume 0.5 x 0.5 x 20 mm 3 was used and applied equal-biaxial stress approach to obtain residual stresses.…”
Section: Strain Analysismentioning
confidence: 99%
“…In the example shown, it was observed that the overall residual stress in the coating was compressive. Also, due to the elevated spray temperature characteristic of low-pressure cold sprayed coatings (dynamic metallization), thermal stresses were also present, and because of the multi-phase composition and thermal mismatch between the metal and ceramic components of the metal matrix composite (MMCs), inter-phase micro-stresses also accumulated, leading to overall compressive residual stresses [55].…”
Section: Strain Analysismentioning
confidence: 99%
“…It was proposed that a deconvolution procedure (i.e., modelling the Gaussian-like distribution of the intensity through the gauge volume may increase the resolution in the interface region. In another example, BT8 instrument at NIST in partnership with KOWARI instrument at ANSTO[55] studied residual stress using BT8 instrument and texture using KOWARI instrument. Such collaboration is good for informed test measurement and guidance along with potential to open new avenue of future research.Neutrons diffraction techniques complement other characterisation techniquesand number of neutron facilities worldwide are considered the most useful for materials of today as well for future new materials.…”
mentioning
confidence: 99%